Elevating the Small and Medium Enterprises at Bongan Village by Optimizing the Use of Gonda Plant - I Gusti Ayu Ari Agustini; Billy Tanius (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
Purpose – This study aimed at exploring the strategies to elevate the small and micro enterprises (SMEs) at Bongan Village by optimizing the use of Gonda Plants as a unique culinary product to support the economic and tourism sector. The supply of Gonda Plants is commonly overflowing every harvest time as Bongan Village is well known for its rice fields. The oversupply of Gonda Plants becomes waste thrown away at the field by the Bongan people but it is the potential to be processed as a unique culinary product. Methodology – The research was carried out using a descriptive qualitative research method in which the data used were obtained through observation, interviews, and literature studies. The interview process involved the Bongan people who are running Gonda Plant SME. The data were analyzed using SWOT analysis to find out the suitable strategies by considering its strengths, weaknesses, opportunities, & threats. Findings – Based on the results of the analysis, the strategies that can be implemented to elevate the enterprises are increasing the skills, knowledge, and motivation to run the SMES, building branding and doing promotion, creating a hygiene production house, improving the management, and being active in grabbing the opportunies. Besides, the involvement of the government and other parties is needed to supervise and mentor the SMEs run by the Bongan people. Novelty – The sustainability of SMEs run by the Bongan people can be done alone, it needs help from other parties, especially the government in guiding, facilitating, and supervising.